ASSESSMENT OF EXTRAPULMONARY TOXICITY INDUCED BY CARBON NANOMATERIALS FOLLOWING INTRA-TRACHEAL INSTILLATION IN RATS - Angoth, Bhikku; Lingabathula, Harikiran; Yellu, NarsimhaReddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Carbon nanomaterials (CNMs) such as carbon nanofibres (CNFs), multi wall carbon nanotubes (MWCNTs) and carbon nanorods (CNRs) were found various industrial and commercial applications. The occupational exposure for these CNMs were also increased enormously. The present study evaluated the extrapulmonary toxicity induced by these CNMs.Â  Methods: The extrapulmonary toxicity was assessed following intratracheal instillation of test CNMs in rats after 1 day, 1 week, 1 month and 3 months post exposure periods by using serum biochemical parameters such as alanine transaminase (ALT) and creatinine using diagnostic assay kits. Further, the histopathological analysis was performed for liver and kidneys of particle exposed rats. Results: The results have displayed that increased levels of serum ALT and creatinine were found after 1 day, 1 week and 1 month post exposure periods indicating liver and kidney toxicity respectively. This toxicity was further confirmed by the changes observed in the histopathological analysis of rat liver and kidneys. Conclusion: The CNFs, MWCNTs and CNRs able to translocate from the lungs into other extrapulmonary organs such as liver and kidney, and also cause dose dependent toxicity to them.